Rare Tumors In Children and Adolescents - Schneider, Dominik; Brecht, Ines B.; Olson, Thomas A.; Ferrari, Andrea (Springer Berlin Heidelberg, 2012)
This is the first book to be devoted exclusively to rare tumors in children and adolescents, and its aim is to provide up-to-date information on their diagnosis and clinical management. The opening section of the book addresses general issues including epidemiology, risk factors/etiology, biology and genetics, prevention, early detection, and screening. It also discusses solutions to assist in the management of rare tumors, such as international networking and internet platforms, thus providing the reader with access to the developing clinical network for rare tumors in children. In the second section, specific malignancies are described, with practical guidance on diagnostic workup, multimodal therapy, survival outcome, follow-up, and adverse effects. These chapters are organized by site according to the clinician's approach to the patient. Each chapter includes an introduction to the differential diagnostic assessment of tumors at the site in question, encompassing both frequent and rare tumor types. This approach should enable the clinician to take rare entities into account during the diagnostic assessment, so that the initial diagnostic steps are performed optimally. Each chapter goes on to provide detailed therapeutic guidelines for specific rare tumors. The authors are a multidisciplinary group of specialists who have dedicated themselves to this group of tumors. This well-illustrated book will prove an invaluable source of information for all pediatricians and oncologists faced with the often difficult task of diagnosing and treating rare tumors in the pediatric age group
Keywords: Oncology; Surgical Oncology; Pediatrics; Oncology; Surgical oncology; Kind; Jugend; Tumor; Aufsatzsammlung